2008
DOI: 10.1111/j.1756-2171.2008.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect durability and the Coase conjecture

Abstract: This paper considers a market served by a monopolist who sells a durable goods that depreciates stochastically over time. We show that there exist three types of stationary equilibria: a Coase Conjecture equilibrium, a monopoly equilibrium and a reputational equilibrium. When the depreciation rate is low, the Coase Conjecture equilibrium is the unique equilibrium. For intermediate values of the depreciation rate, all three equilibrium types coexist. When the depreciation rate is high, the monopoly equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In each period, the game runs as follows. First, the monopolist sets the 1 The specific case where u H = u L and u H = u L hold is studied by [9].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In each period, the game runs as follows. First, the monopolist sets the 1 The specific case where u H = u L and u H = u L hold is studied by [9].…”
Section: Modelmentioning
confidence: 99%
“…However, reference [8] also shows the existence of an equilibrium that verifies the Coase conjecture. Then, reference [8,9] characterize the effect of the depreciation rate on the market outcome of a durable goods monopoly when agents follow Markov strategies. They conclude that, below a certain level of durability, there exists a unique stationary equilibrium in which the monopolist charges the static monopoly price in each period and the equilibrium continues to exist even when the seller becomes highly impatient.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include fixed capacity (Bulow 1982), increasing marginal cost (Kahn 1986), reputation formation (Ausubel and Deneckere 1989), and contractual provisions such as most-favored-customer and best-price clauses (Butz 1990). More recently Deneckere and Liang (2008) showed that finite durability of the good (planned obsolescence) prevents emergence of Coase's equilibrium.…”
Section: Quality and Intertemportal Price Discriminationmentioning
confidence: 99%
“…5. For instance, see Bulow (1986), Bagnoli et al (1989) or Deneckere and Liang (2008);Waldman (2003) surveys.…”
Section: Introductionmentioning
confidence: 99%